2019
DOI: 10.1093/cercor/bhz303
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Cortical Parcellation Based on Diffusion MRI Tractography

Abstract: The spatial topological properties of cortical regions vary across individuals. Connectivity-based functional and anatomical cortical mapping in individuals will facilitate research on structure–function relationships. However, individual-specific cortical topographic properties derived from anatomical connectivity are less explored than those based on functional connectivity. We aimed to develop a novel individualized anatomical connectivity-based parcellation framework and investigate individual differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…Recently, Han et al. found that the individual-specific parcels derived from WM tractography at the individual level generated more homogeneous connectivity pattern than the population atlas ( Han et al. 2019 ), suggesting the advantage of the personalized parcellation in characterizing the individual differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Han et al. found that the individual-specific parcels derived from WM tractography at the individual level generated more homogeneous connectivity pattern than the population atlas ( Han et al. 2019 ), suggesting the advantage of the personalized parcellation in characterizing the individual differences.…”
Section: Discussionmentioning
confidence: 99%
“…Since individualized segmentation would better characterize individual diversities in development, cognition, and behavior ( Mueller et al. 2013 ; Han et al. 2019 ; Kong et al.…”
Section: Introductionmentioning
confidence: 99%
“…The iterative clustering method can be seen in Supplementary Methods). The original method with the anatomical connectivity was applied on image volume space [30], we adjusted it on individual cortical surface space, details of the method can be seen in Supplementary Methods.…”
Section: B Group-registered and Iterative Clustering Methodsmentioning
confidence: 99%
“…Many studies adopted cortical fingerprint-based (e.g., anatomical and functional connectivity) mappings for individualizing the population atlas to reveal individualspecific variability of cortical areas [13,[25][26][27][28][29][30][31][32][33]. Population atlas priors provide a blueprint of functional and anatomical architectures of the human brain in these mappings to guide individual-specific topography presented by connection fingerprints [13,23,26,[32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation